Horatio King papers - King, Horatio, 1811-1897.
Correspondence relating primarily to the U.S. Post Office Dept.; Democratic Party; politics; legislation; patronage; the secession crisis of 1860-1861; King's literary, historical, and social activities; and social life in Washington, D.C., in the latter half of the 19th century. Correspondents include Adam Badeau, Chauncey F. Black, James Buchanan, Nahum Capen, Schuyler Colfax, Andrew Gregg Curtin, George Ticknor Curtis, J.C. Bancroft Davis, John A. Dix, William Maxwell Evarts, John W. Forney, Edward Miner Gallaudet, Hannibal Hamlin, William Harkness, Joseph R. Hawley, Joseph Holt, John James Ingalls, Harriet Lane Johnston, De B. Randolph Keim, George Kennan, Robert Todd Lincoln, Hugh McCulloch, Justin S. Morrill, Levi P. Morton, Crosby Stuart Noyes, Franklin Pierce, Benjamin Perley Poore, Fitz-John Porter, Daniel Edgar Sickles, Ainsworth Rand Spofford, John C. Spooner, Moses Coit Tyler, John Wanamaker, and Robert C. Winthrop. Also includes correspondence of his son, Horatio C. King, with Fitz-John Porter and Daniel Edgar Sickles.
U.S. postmaster general, editor, and author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Badeau, Adam, -- 1831-1895 -- Correspondence; Black, Chauncey F. -- Correspondence; Buchanan, James, -- 1791-1868 -- Correspondence; Capen, Nahum, -- 1804-1886 -- Correspondence; Colfax, Schuyler, -- 1823-1885 -- Correspondence; Curtin, Andrew Gregg, -- 1815-1894 -- Correspondence; Curtis, George Ticknor, -- 1812-1894 -- Correspondence; Davis, J. C. Bancroft -- 1822-1907 -- Correspondence; Dix, John A. -- 1798-1879 -- Correspondence; Evarts, William Maxwell, -- 1818-1901 -- Correspondence; Forney, John W. -- 1817-1881 -- Correspondence; Gallaudet, Edward Miner, -- 1837-1917 -- Correspondence; Hamlin, Hannibal, -- 1809-1891 -- Correspondence; Harkness, William, -- 1837-1903 -- Correspondence; Hawley, Joseph R. -- 1826-1905 -- Correspondence; Holt, Joseph, -- 1807-1894 -- Correspondence; Ingalls, John James, -- 1833-1900 -- Correspondence; Johnston, Harriet Lane, -- 1830-1903 -- Correspondence; Keim, De B. Randolph -- 1841-1914 -- Correspondence; Kennan, George, -- 1845-1924 -- Correspondence; King, Horatio C. -- 1837-1918 -- Correspondence; Lincoln, Robert Todd, -- 1843-1926 -- Correspondence; McCulloch, Hugh, -- 1808-1895 -- Correspondence; Morrill, Justin S. -- 1810-1898 -- Correspondence; Morton, Levi P. -- 1824-1920 -- Correspondence; Noyes, Crosby Stuart, -- 1825-1908 -- Correspondence; Pierce, Franklin, -- 1804-1869 -- Correspondence; Poore, Benjamin Perley, -- 1820-1887 -- Correspondence; Porter, Fitz-John, -- 1822-1901 -- Correspondence; Sickles, Daniel Edgar, -- 1825-1914 -- Correspondence; Spofford, Ainsworth Rand, -- 1825-1908 -- Correspondence; Spooner, John C. -- 1843-1919 -- Correspondence; Tyler, Moses Coit, -- 1835-1900 -- Correspondence; Wanamaker, John, -- 1838-1922 -- Correspondence; Winthrop, Robert C. -- 1809-1894 -- Correspondence; United States. -- Post Office Department; Democratic Party (U.S.); Patronage, Political -- United States; Secession; United States -- Intellectual life -- 19th century; United States -- Politics and government -- 19th century; Washington (D.C.) -- Social life and customs; Authors; Cabinet officers; Editors